Phenotypic shifts induced by environmental pre-stressors modify antibiotic resistance in Staphylococcus aureus - Wee, Gui Nam; Lyou, Eun Sun; Nishu, Susmita Das; Lee, Tae Kwon (Frontiers in Microbiology, 2023)
Introduction Escalating prevalence of antibiotic resistance in Staphylococcus aureus has necessitated urgent exploration into the fundamental mechanisms underlying antibiotic resistance emergence, particularly in relation to its interaction with environmental stressors. This study aimed to investigate the effects of environmental stressors prior to antibiotic exposure on the antibiotic resistance of S. aureus. Methods We used Raman spectroscopy and flow cytometry to measure prior stress-induced phenotypic alterations of S. aureus, and identified the association between phenotypic shifts and the antibiotic resistance. Results The results revealed a multifaceted relationship between stressors and the development of antibiotic resistance. The stressors effectuate distinct phenotypic diversifications and subsequently amplify these phenotypic alterations following antibiotic treatments, contingent upon the specific mode of action; these phenotypic shifts in turn promote the development of antibiotic resistance in S. aureus. This study’s findings demonstrated that the presence of pre-stress conditions triggered an augmentation of resistance to vancomycin (VAN), while concurrently attenuating resistance to norfloxacin. Marked shifts in Raman peaks associated with lipids and nucleic acids demonstrated correlations with elevated survival rates following VAN treatment. Conclusion Consequently, these observations indicate that pre-stress conditions “prime” bacterial cells for differential responses to antibiotics and bear significant implications for formulating clinical therapeutic strategies.